Implementation of the Pelagic Hotspot Index in detecting the habitat suitability area for bigeye tuna (Thunnus obesus) in the eastern Indian Ocean - ZABHIKA DINDA ISTNAENI; JONSON LUMBAN GAOL; MUKTI ZAINUDDIN; DEVI FITRIANAH (Society for Indonesian Biodiversity, 2023)
Abstract. Istnaeni ZD, Gaol JL, Zainuddin M, Fitrianah D. 2023. Implementation of the Pelagic Hotspot Index in detecting the habitat suitability area for bigeye tuna (Thunnus obesus) in the eastern Indian Ocean. Biodiversitas 24: 5044-5056. Bigeye tuna (Thunnus obesus Lowe, 1839) is a species with a high economic value that can migrate horizontally and vertically over a large area. Although sea temperature has been the main focus of previous findings, other variables can serve as a reasonable proxy. Here we used sea surface chlorophyll-a, sea surface height, subsurface sea salinity, and subsurface temperature to predict the suitable habitat area for bigeye tuna in the Eastern Indian Ocean Off Java. A Generalized Additive Model was performed to analyze the best-fit model evaluated from the p-value and Cumulative Deviance Explained. The suitability index of the selected model was calculated using Pelagic Hotspot Index constructed from multi-spectrum satellite data. The results showed that the high catches were located on the high suitable index value and supported by chlorophyll-a as the most significant factor, followed by sea surface height, temperature, and salinity. This condition was stimulated by the high feeding opportunity, which may relate to the EIO's oceanic front, eddies, and specific current patterns. This study helps identify ecological hotspots, track the migration, and monitor the seasonal closure for bigeye tuna, particularly in EIO.